1982
DOI: 10.1007/bf00521290
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of the effects of erythromycin on the morphology and developmental cycle of Chlamydia trachomatis HAR-13

Abstract: The effect of erythromycin (10 micrograms/ml) on the morphology and developmental cycle of Chlamydia trachomatis HAR-13 was examined by electron microscopy. When the antibiotic was added later than 24 h post infection, the HAR-13 morphology or developmental cycle was not altered. Addition at 18 or 24 h post infection inhibited glycogen production, blocked the transformation of the reticulate body to elementary body, and produced ghost bodies and reticulate bodies twice the diameter of untreated reticulate bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…In general, agents that target bacterial protein or RNA synthesis can inhibit chlamydial differentiation either from EB to RB or from RB to EB, depending on when they are added to an in vitro infection, whereas those that target DNA or peptidoglycan synthesis specifically inhibit RB-to-EB differentiation (78). For example, 10 g of erythromycin/ml, which reduces ribosome activity, inhibited C. trachomatis serovar A EB-to-RB differentiation in McCoy cells when added within 12 h PI (24). When the erythromycin was applied at later times PI, infections were established featuring enlarged RB that could not differentiate to EB (24).…”
Section: Chlamydial Persistence In Vitromentioning
confidence: 99%
“…In general, agents that target bacterial protein or RNA synthesis can inhibit chlamydial differentiation either from EB to RB or from RB to EB, depending on when they are added to an in vitro infection, whereas those that target DNA or peptidoglycan synthesis specifically inhibit RB-to-EB differentiation (78). For example, 10 g of erythromycin/ml, which reduces ribosome activity, inhibited C. trachomatis serovar A EB-to-RB differentiation in McCoy cells when added within 12 h PI (24). When the erythromycin was applied at later times PI, infections were established featuring enlarged RB that could not differentiate to EB (24).…”
Section: Chlamydial Persistence In Vitromentioning
confidence: 99%
“…Other antibiotics have also been reported to induce abnormal chlamydial development. Erythromycin, when used in subinhibitory concentrations, produced small inclusions of C. trachomatis, with RBs twice the size of typical RBs (6). Treatment of C. trachomatis with sulfonamides induced development of small inclusions containing irregular RBs with ruffled membranes, mini-RB-like forms, and numerous ghost particles (10,12).…”
mentioning
confidence: 98%
“…Persistent chlamydial infections can be established in vitro using several methods, including treatment with cytokines (2,4,16,18) or antibiotics (5,6) or by deprivation of certain nutrients (13). In all cases they have been described as having morphologically abnormal reticulate bodies (RBs), which suggests that they are somehow altered during their otherwise normal development.…”
mentioning
confidence: 99%
“…To induce persistence, we added penicillin as described elsewhere (Clark et al, 1982). The persistent state of C. trachomatis upon penicillin exposure at 24 h p.i.…”
Section: Cl-55 Lyses Aberrant Chlamydial Forms Induced By Penicillinmentioning
confidence: 99%
“…Research from multiple teams has demonstrated that an encounter with specific stimuli can transform Chlamydia into a third state called 'persistence' (Clark et al, 1982;Harper et al, 2000), which has been defined as a reversible interruption of productive intracellular chlamydial growth mediated by environmental factors (Beatty et al, 1994). Persistence is an alternative outcome of a productive bacterial infection where a subpopulation of the bacteria becomes 'invisible' in response to prolonged antibiotic treatment, warding off innate and adaptive immune responses, causing little or no symptoms in the infected host, and possibly unnoticed by the diagnostician (Bavoil et al, 2000).…”
Section: Introductionmentioning
confidence: 99%